The Street Food Paradox: Risk, Attraction, and the Quest for Culinary Satisfaction - Utama, Iston Dwija; Sari, Diana; Helmi, Arief; Sembada, Agung Yoga (Journal of Ecohumanism, 2025)
This study investigates the influence of perceived risks and motivations on tourist behavior and satisfaction in Indonesia's street food tourism context. Using a quantitative method with stratified random sampling and using Structural Equation Modeling (SEM), it analyzes data from tourists in Indonesia's urban street food settings. The findings indicate that perceived risks do not directly inhibit tourists' behavioral intentions but significantly affect both push and pull motivations, suggesting that risks can both discourage and strengthen the street food tourism experience. Contrary to some prior studies, pull motivation does not directly impact behavioral intention but significantly influences satisfaction, highlighting the importance of external factors like ambiance and authenticity. Push motivation, conversely, has a notable effect on behavioral intention, pull motivation, and satisfaction. A strong correlation between satisfaction and behavioral intention is observed, emphasizing satisfaction's key role in predicting future tourist behaviors. The study also discusses its limitations and suggests directions for future research.